1969
DOI: 10.1161/01.res.25.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ouabain on Insulin Secretion in the Dog

Abstract: The mechanism of the previously reported hypoglycemic effect of ouabain was studied in dogs. Ouabain (1.0 /xg/kg/min infused intravenously for 60 minutes) combined with insulin or propranolol caused a greater and more prolonged decrease in blood glucose than either of the drugs administered separately. In intact dogs, ouabain changed significantly portohepatic venous differences in plasma glucose from +6.6 to -13.6 mg/100 ml and in K + from -0.03 to -0.4 mEq/liter. In pancreatectomized animals, ouabain did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The Na-K pump is located in the plasma membrane of all animal cells and functions to pump sodium outward and potassium inward. Ouabain increases insulin secretion as an Na-K pump inhibitor 36, 37 . However, it remains unknown whether the insulin secretion increased by ouabain is dependent on K ATP channels.…”
Section: Resultsmentioning
confidence: 99%
“…The Na-K pump is located in the plasma membrane of all animal cells and functions to pump sodium outward and potassium inward. Ouabain increases insulin secretion as an Na-K pump inhibitor 36, 37 . However, it remains unknown whether the insulin secretion increased by ouabain is dependent on K ATP channels.…”
Section: Resultsmentioning
confidence: 99%
“…Triner, Kypson & Nahas (1968) reported that the intravenous infusion of ouabain in a dose of 1 pglmin-' kg-' for 1 h resulted in a significant decrease (30%; P<0*05) of blood glucose concentration in anaesthetized dogs. Loubatieres et al (1968) and Triner et al (1969) subsequently demonstrated that the fall in blood glucose concentration observed during similar ouabain infusions was associated with a significant increase in plasma insulin concentration in the portal vein. However, both groups used doses four times greater than that used in the present studies, the maximum safe dose in man, whereas Milner & Hales (1967) used concentrations of ouabain 400 times greater.…”
Section: Discussionmentioning
confidence: 96%
“…Ouabain is capable of stimulating the release of insulin from tissue slices of rabbit pancreas (Milner & Hales, 1967) and from the pancreas of the anaesthetized dog (Loubatieres, Mariani, Sonel & Sonel, 1968;Triner, Papayoanou, Killian, Vulliemoz, Castany & Nahas, 1969). This is of considerable clinical interest in the light of the recent finding that insulin secretion is suppressed in patients with severe heart failure (Sharma, Majid, Pakrashi, Dykes & Taylor, 1970;Majid, Saxton, Dykes, Galvin & Taylor, 1970), particularly as digitalis glycosides are frequently employed in the treatment of these patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is synergistically enhanced by addition of insulin. Furthermore, ouabain induces increased secretion of insulin and in vitro inhibits the metabolic effects of epinephrine [80]. A clear-cut stimulatory effect of ouabain on the production of insulin in the anesthetized dog has been demonstrated in both infusion and “one shot” experiments [81].…”
Section: Cardiotonic Glycosides Induce Vagus-mediated Amplification Omentioning
confidence: 99%